Home humidity increased risk of tuberculosis in children living with adult active tuberculosis cases - Lestari, Pudji; Sustini, Florentina; Endaryanto, Anang; Asih, Retno (Universa Medicina, 2011)
Indonesia is one of the countries with the largest number of tuberculosis (TB) cases in the world. Environmental factors play significant roles in infection and disease development in children living with adult active TB cases. The aim of this study was to explore the environmental factors affecting TB risk in children, including humidity and number of people living in the same house with the children.Â  Using a cross-sectional study design, children living with active TB adults for at least 8 weeks were recruited. The subjects underwent clinical examination, tuberculin skin test (TST) and radiological investigations. Home visits were conducted three times daily, namely in the morning, at midday, and in the evening, to measure humidity by digital hygrometer and to observe home conditions. Of 56 index cases living with active TB adults in an urban low socio-economic setting, 64 contact TB children were recruited. These children were classified as class I with negative TST and no clinical signs, class II with positive TST and no clinical signs, and class III with both positive TST and clinical signs. There were 32 (50%) class I, 10 (15.6%) class II and 22 (34.3%) class III children. However, a sub-sample of 43 showed positive results for Mtb 16S rRNA, indicating that all children were infected. The humidity cut-off point was set at 75%, p=0.04 and EP 2.09 (CI= 1.32-3.29), signifying that children living in houses with a humidity higher than 75%, were twice more likely to be tuberculin positive. Environmental conditions playing a role in disease development were humidity and number of people living in the house.